P3.82 An upward trend in ocular syphilis cases in british columbia, canada, 2013–2016: a descriptive analysis. (8th July 2017) - Shumilak, G; Wong, J; Arnold, B; Gilbert, M; Lukac, C; Makaroff, S; Montgomery, C; Moore, D; Prescott, C; Grennan, T
Abstract : Introduction: HIV-positive individuals are generally considered higher risk for early and more serious neurologic complications related to syphilis. In 2014–2015, clusters of ocular syphilis cases were reported in the US. Simultaneously, the Canadian province of British Columbia (BC) saw a dramatic rise in infectious syphilis cases by 40%. Here, we describe ocular syphilis cases diagnosed in BC. Methods: All neurosyphilis cases diagnosed in BC since 2013 were reviewed to identify ocular cases. Ocular syphilis was defined as having signs/symptoms of ocular disease (e.g. uveitis, blurred vision) and syphilis of any stage, as defined by the Centres for Disease Control and Prevention. Results: Between January 1 st, 2013 and October 31 st, 2016, 35 cases of ocular syphilis were recorded in BC. Most were male (32/35; 91.4%) and identified as white (20/35; 57.1%). The mean age was 49.7 years. A majority (18/35; 51.4%) were living with HIV. The most frequent ophthalmologic diagnoses were uveitis (41.9%), optic neuritis (12.9%), and retinitis (9.7%). Twenty-three cases had lumbar puncture data available: 13 (56.5%) had elevated cerebrospinal fluid (CSF) protein, 15 (65.2%) had elevated CSF cell count, and 6 (26.1%) had positive CSF VDRL. As a proportion of all syphilis cases, ocular syphilis accounted for 0.80% of all cases during the 2013–2015 period, versus 1.54% for 2016 (p=0.05). Stratified by HIV serostatus, there was a significant increase in the proportion of ocular syphilis cases in those living with HIV between the 2013–2015 and 2016 time periods (1.17% vs. 3.21%, p=0.03). Conclusion: Paralleling trends observed in some US jurisdictions, BC is experiencing an increase in ocular syphilis cases, and an increasing proportion of syphilis cases in those living with HIV are being diagnosed with ocular findings. These results further highlight the importance of continuing efforts to respond to the syphilis epidemic, and focused screening for ocular symptoms, particularly in those at highest risk.